DISTANCE LEARNING COURSE IN BLENDED BILATERAL INTERPRETING EDUCATION BASED ON NATIONAL ESP CURRICULUM - Гурєєва, Л. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is dedicated to the modern issues of technology development and distance learning courses combining traditional elements with modern teaching methods. The author has identified the need for introducing blended learning to enhance translation competence of foreign language students. The distance learning course with microlearning elements developed for students of the National Technical University of Ukraine “Igor Sikorsky Kyiv Polytechnic Institute” to improve the bilateral interpreting skills of the final-year undergraduate students (035 Philology) is described. The paper outlines the main problems of perception of distance courses describing the solutions for the effective implementation of the course in teaching practice